(untitled) (Research, Society and Development, 2023)
The occupation of slopes is quite recurrent in several Brazilian regions. For the most part, this occupation takes place irregularly, without adequate planning. In this way, the natural characteristics of the area, together with anthropic actions inappropriate to the use and occupation of the land, end up causing mass movements, which can seriously affect the local community. In Natal, Rio Grande do Norte, this reality is also verified, as is the case in the Mãe Luíza neighborhood. Faced with this scenario, the objective of this study was to carry out a risk mapping of mass movements in an area belonging to the Mãe Luíza neighborhood, between Rua Camaragibe and Rua Atalaia. The risk mapping of the area under study was carried out based on the methodology proposed by Brasil (2007). Four risk classes were defined, these being low, medium, high and very high risk. Three critical areas were analyzed, with thirty-four properties involved. Among these, only six were classified as having medium mass movement risk, twenty-four properties were classified as high risk and four properties classified as very high risk. The high degree of risk attributed to most properties is mainly due to the precariousness of the existing containment structures in the area under study, associated with irregular constructions, among other factors. Thus, it is evident the need for corrective measures of the situations found to guarantee the habitability of the inspected properties, in addition to public policies to control the occupation of risk areas.